The extent to which high school students need pedagogical accompaniment as a form of academic guidance: A field study on a sample of high school students in Constantine "Asia Jabbar" - SAADI, Rofia; REMADNIA, Ahmed (Social Sciences Journal, 2021)
In this scientific paper, we dealt with the subject of pedagogical accompaniment as a kind of academic guidance from the perspective of high school students to the professors, as a highly educational and special character that does not belong to the classical system nor to the lmd system characterizes them. The extent to which high school students need professors for educational accompaniment through a set of dimensions by our application of the descriptive and analytical curriculum and by using the semi-directed interview tool, which included five questions and this tool was applied to a sample of high school students for professors. The students of the graduate student at the University of "Asia Jabbar", which included 84 students in the elementary stage, and we concluded a set of results that prove the importance of pedagogical accompaniment in all stages of the university, especially those related to the pedagogical and professional aspect, psychological preparation and skills to enter the state of work and the students’ need for pedagogical accompaniment. They enable them to overcome the obstacles and problems that face them in the graduation years, especially with the presence of a positive trend from students towards the subject of pedagogical accompaniment at the university.